Pengembangan Dan Validasi Metode Analisis Tablet Furosemid Dengan Metode Absorbansi Dan Luas Daerah Di Bawah Kurva Secara Spektrofotometri Ultraviolet - Ridho Asra; Harrizul Rivai; Via Lovita Riani (Jurnal Farmasi Higea, 2016)
Development and validation of analysis methods of furosemide tablet have been done by absorbance method and area under the curve methods using ultraviolet spectrophotometry. Linearity of pure furosemide was obtained with range concentration 8 - 18 ppm. Coefficient correlations absorbance and area under curve methods were 0.99999 and 0.99725 respectively. The percentage of stated content were determined, which were compared with Gralixa Furosemide tablets and generic furosemid tablets. The results showed that the percentage of stated content from Gralixa tablet with absorbance and the area under curve methods were 99,33 % ± 0,004 and 98,44 % ± 0,003 and the recovery were 98,75 % and 97,88 % respectively. While the research results showed that the percentage of stated content from generic furosemide tablets with absorbance and area under curve methods were 98,42 % ± 0,005 and 97,78 % ± 0,008 and the recovery were 98,61 % and 95,06 %. Statistical analysis proves that the method is reproducible and selective for the analysis of furosemide.